Formulation optimization of aprepitant microemulsion-loaded silicated corn fiber gum particles for enhanced bioavailability. (2nd August 2016) - Kamboj, Sunil; Rana, Vikas
Abstract: The present investigation was aimed at development of silicate corn fiber gum (SCFG) particles as superior solid carrier for the preparation of Aprepitant (APT)-loaded self-emulsifying powder (SEP) system. 2 4 D-optimal mixture design with three level process variables was employed to develop SCFG particles, utilizing flow descriptors and hydrophobicity descriptors as response variables. The results indicated that blending of CFG (51.4% w/w) and magnesium silicate (MS) (48.6% w/w) using freeze-drying technique was found to have highest desirability (0.904). The developed SEP showed highest oil desorbing capacity, low self-emulsification time and highest drug content. It was observed that SCFG-SEP (F2 formulation) showed lowest PDI (0.2445 ± 0.03) as well as smallest particle size (127 ± 5.8 nm). The droplets were uniform and maintain their integrity after reconstitution (TEM analysis). Furthermore, APT-loaded SEP showed enhanced in vitro dissolution (4 folds) and ex vivo performance (7-fold enhanced P app ) as compared to pure APT. Furthermore, in vivo pharmacokinetic study showed that significant enhancement ( p > 0.05) in C max was evident with APT-loaded F2 (SCFG-SEP) (1.93-fold) and F4 (Aerosil 200-SEP) (1.58-fold). The data also suggested increase in absorption rate when APT incorporated into SCFG-SEP. Thus, findings pointed toward enhanced bioavailability of APT when loaded into SCFG particles. Overall, the developed SCFG particles could be considered as a better alternative to already available solid carrier(s).